COMPETITIVENESS OF POLISH AND SLOVAK AGRI-FOOD PRODUCTS ON THE EUROPEAN MARKET - Anna Rytko (Polityki Europejskie, Finanse i Marketing)
The aim of this paper was to define the Polish and Slovak competitiveness position of agricultural and food products on the European market, as well as for comparison purposes, on the markets of the third countries and to the other groups of products. However, the issue was show the changes of the competitiveness in this sector. The competitiveness performance in Polish and Slovak agrofood trade has been evaluated for the period of 1999-2012. Trade theories indicate that countries specialize in the production of goods, trade in these goods and have better competitiveness position, if they have an absolute or comparative advantages in relationship to your partner (Ricardo 1957, Balassa 1965, Lall 2001, Guzek 2006). In order to determine the competitive position, the comparative advantage and evaluation of agrofood trade were used. The analysis considers two indices: revealed comparative advantage (RCA) and net export index (NEI). After joining the European Union, the importance of foreign agro-food trade in both of this countries has grew up in European market, but on the third countries market only Poland notified increases. The index of RCA in these countries is quite different. It is observed comparative advantage in Poland while in Slovakia there was not. Similar situation was in NEI index. A positive value of the net export index for agri-food products was found only in Poland.